A two-phase solver for complex fluids: Studies of the Weissenberg effect. (September 2016) - Figueiredo, R.A.; Oishi, C.M.; Afonso, A.M.; Tasso, I.V.M.; Cuminato, J.A.
Highlights: We propose an axisymmetric solver for two-phase viscoelastic fluid flows. The method can be used for solving viscoelastic problems at a wide range of Weissenberg numbers. The numerical algorithm is assessed for several benchmark tests from the Computational Rheology literature. A detailed numerical study of the Weissenberg or Rod-Climbing effect is presented. Transient peculiar behaviors observed in the Weissenberg effect problem are numerically captured, as for example, the "breathing instability". Graphical abstract: Abstract: In this work a new two-phase solver is presented and described, with a particular interest in the solution of highly elastic flows of viscoelastic fluids. The proposed code is based on a combination of classical Volume-of-Fluid and Continuum Surface Force methods, along with a generic kernel-conformation tensor transformation to represent the rheological characteristics of the (multi)-fluid phases. Benchmark test problems are solved in order to assess the numerical accuracy of distinct levels of physical complexities, such as the interface representation, the influence of advection schemes, the influence of surface tension and the role of fluid rheology. In order to demonstrate the new features and capabilities of the solver in simulating of complex fluids in transient regime, we have performed a set of simulations for the problem of a rotating rod inserted into a container with a viscoelastic fluid, known as the Weissenberg or Rod-Climbing effect. Firstly, our results are compared with numerical and experimental data from the literature for low angular velocities. Secondly, we have presented results obtained for high angular velocities (high elasticity) using the Oldroyd-B model which displayed very elevated climbing heights. Furthermore, above a critical value for the angular velocity, it was observed the onset of elastic instabilities driven by the combination of elastic stresses, interfacial curvature and secondary flows, that to the authors best knowledge, were not yet reported in the literature.